Accelerated growth of B16BL6 tumor in mice through efficient uptake of their own exosomes by B16BL6 cells. Issue 9 (21st July 2017) - Matsumoto, Akihiro; Takahashi, Yuki; Nishikawa, Makiya; Sano, Kohei; Morishita, Masaki; Charoenviriyakul, Chonlada; Saji, Hideo; Takakura, Yoshinobu
Abstract : Exosomes are extracellular vesicles released by various cell types and play roles in cell–cell communication. Several studies indicate that cancer cell‐derived exosomes play important pathophysiological roles in tumor progression. Biodistribution of cancer cell‐derived exosomes in tumor tissue is an important factor for determining their role in tumor proliferation; however, limited studies have assessed the biodistribution of exosomes in tumor tissues. In the present study, we examined the effect of cancer‐cell derived exosomes on tumor growth by analyzing their biodistribution. Murine melanoma B16BL6‐derived exosomes increased the proliferation and inhibited the apoptosis of B16BL6 cells, which was associated with an increase and decrease in the levels of proliferation‐ and apoptosis‐related proteins, respectively. GW4869‐induced inhibition of exosome secretion decreased the proliferation of B16BL6 cells, and treatment of GW4869‐treated cells with B16BL6‐derived exosomes restored their proliferation. Next, we treated B16BL6 tumors in mice with B16BL6‐derived exosomes and examined the biodistribution and cellular uptake of these exosomes. After the intratumoral injection of radiolabeled B16BL6‐derived exosomes, most radioactivity was detected within the tumor tissues of mice. Fractionation of cells present in the tumor tissue showed that fluorescently labeled exosomes were mainly taken up by B16BL6 cells. Moreover, intratumoral injection of B16BL6‐derived exosomes promoted tumor growth, whereas intratumoral injection of GW4869 suppressed tumor growth. These results indicate that B16BL6 cells secrete and take up their own exosomes to induce their proliferation and inhibit their apoptosis, which promotes tumor progression. Abstract : Biodistribution and cellular uptake of cancer cell‐derived exosomes were analyzed. Cancer cells efficiently take up their own exosomes to induce tumor progression. Inhibition of exosomes secretion suppressed tumor growth.